Data exchange between the SAP ERP system and local systems of the main production workshops using web services - D. M. Dupanov (Литьë и металлургия, 2022)
The article presents the basic principles of web services. The comparison with other types of web services is carried out. Analyzed the advantages and disadvantages of different solutions. One of the options for software implementation that allows data transfer between the SAP ERP system and the local systems of the main production units using web services is considered. The result of this work was the implementation and adaptation of a new method of data exchange between systems, the possibility of using received classes and functional modules for the quick creation of following-up web services.